UNDERSTANDING THE IMPACT OF HAMSTRING INJURIES ON MATCH PERFORMANCE IN SPANISH PROFESSIONAL SOCCER PLAYERS: TWO FULL SEASONS FOLLOW-UP (Kinesiology, 2023)
This study aimed to analyze the changes in match physical performance in professional soccer players after sustaining a hamstring injury, which was categorized based on injury severity. Seventy-two hamstring injuries involving sixty-four professional soccer players from the Spanish LaLiga™ were considered for this study. All injuries were classified according to their severity as moderate (resulting in eight to 28 missed days) and major (resulting in more than 28 missed days). Mediacoach video-tracking system collected time and external load variables and subsequently compared them between the pre-injury and return-to-play periods. The analyzed variables included distance covered at different velocities (i.e., total distance, at 18-21 km.h−1, at 21-24 km.h−1, and at more than 24 km.h-1), the number of sprints, accelerations, decelerations, and high metabolic load distance (HMLD). The results showed that players with both the moderate and major injuries played fewer minutes after injury (p